On the Path of No-Character: Zeami’s Traces Walked Back and Forward - Hernández Rodríguez, Álvaro Iván (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
This essay thinks through the journey of being and becoming a character, as it is repeated over decades, focusing on the experience of the author performing his monologue Los Nueve Monstruos (itself based on a poem by Cesar Vallejo). The repeated performance of this monologue over three decades becomes a way of feeling and registering the change of the body and self through the iterative taking-form of a character. The essay reflects upon the changes produced in both the character and the performer during those many encounters over the years, first in Putumayo with the Kamentsa Indigenous peoples, then over the Andes to Colombia’s capital city of Bogotá, and across both the Atlantic and Pacific to Europe and Asia. Embodied encounters of the performer/author with the Noh tradition of Japan and Zeami’s philosophical approach to performance transforms Los Nueve Monstruos—moving from the approximation of the idea of a character to the notion of no-character, a concept of transition that focuses on the vibratory quality and sounding experience of “in-provisation.”